2010
DOI: 10.1161/circimaging.109.888354
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Systolic Strain Rate Predicts Postoperative Left Ventricular Dysfunction in Patients With Chronic Aortic Regurgitation

Abstract: Background-The best predictor for postoperative left ventricular (LV) systolic dysfunction in patients with chronic aortic regurgitation is still a matter of debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…21,22 The sensitivity of these measures to alterations in deformation has resulted in their application, in both animal and human studies, to a variety of pathological conditions characterized by myocardial dysfunction despite preserved EF, including asymptomatic carriers of hypertrophic cardiomyopathy sarcomeric mutations, 23 Fabry's disease, 24 myocardial steatosis, 25,26 and rodent models of Duchenne muscular dystrophy. 27 Perhaps because of their less load-dependent nature, these measures have also proven informative in the setting of valvular heart disease in which alterations in loading conditions make EF a less reliable measure of contractile function, including severe aortic stenosis, 28 aortic regurgitation, 29 and mitral regurgitation. 30 In the case of coronary disease, global strain values obtained early after an acute myocardial infarction may effectively predict subsequent remodeling and functional recovery.…”
Section: Deformation Imaging As a Measure Of LV Function Detection Ofmentioning
confidence: 99%
“…21,22 The sensitivity of these measures to alterations in deformation has resulted in their application, in both animal and human studies, to a variety of pathological conditions characterized by myocardial dysfunction despite preserved EF, including asymptomatic carriers of hypertrophic cardiomyopathy sarcomeric mutations, 23 Fabry's disease, 24 myocardial steatosis, 25,26 and rodent models of Duchenne muscular dystrophy. 27 Perhaps because of their less load-dependent nature, these measures have also proven informative in the setting of valvular heart disease in which alterations in loading conditions make EF a less reliable measure of contractile function, including severe aortic stenosis, 28 aortic regurgitation, 29 and mitral regurgitation. 30 In the case of coronary disease, global strain values obtained early after an acute myocardial infarction may effectively predict subsequent remodeling and functional recovery.…”
Section: Deformation Imaging As a Measure Of LV Function Detection Ofmentioning
confidence: 99%
“…The chronic effects of abnormal loading from valvular disease on myocardial function may be difficult to detect by conventional means, and strain imaging may play a role (61)(62)(63)(64)(65)(66)(67). Delgado et al (62) demonstrated that patients with severe aortic stenosis and preserved EF exhibited decreased radial, circumferential, and longitudinal speckle tracking strain.…”
Section: Applications Of Strain Imaging For Effects Of Valvular Heartmentioning
confidence: 99%
“…Therefore, it is not surprising that markers of cardiac dysfunction shown to be associated with poor outcome in mitral regurgitation, such as exercise LV volumes, resting myocardial strain, and resting myocardial strain rate, are also predictors of need for valve surgery in chronic AR. [7][8][9][10][11][12] In contrast, it is unknown whether right ventricular (RV) dysfunction, which seems to be relevant to the outcomes in mitral regurgitation, 13 carries any importance in chronic AR. We have recently developed a framework of assessing incremental value of resting and exercise parameters of both LV and RV function as prognostic parameters of surgical intervention in chronic asymptomatic mitral regurgitation.…”
Section: Clinical Perspective On P 362mentioning
confidence: 99%
“…[8][9][10][11] Although global LV strain is correlated to LVEF, it may be more sensitive in detecting subclinical myocardial dysfunction 24 in the presence of a pathological process such as AR, even when EF is normal. Although LVEF …”
Section: Rest and Exercise LV Dysfunction As A Predictor Of Valve Surmentioning
confidence: 99%